Peer Programs in Post-Secondary Institutions in Canada - Kingsland, Lynda J.; Carr, Rey A. (Canadian Journal of Counselling and Psychotherapy, 2011)
This article presents the results of a Canada-wide survey of post-secondary counselling centres as to their involvement in peer programs. Seventy-eight per cent of the sample responded and the results are reported by institutional type, program type, number of trained student helpers, the length of training, and sources of funding.